Konsep Wajah, Tanggung Jawab Etis, dan Implikasinya terhadap Problem Kemanusiaan: suatu Telaah Pemikiran Etika Emmanuel Levinas - Jatayu Jiwanda DL (Jurnal Pelita Dharma, 2019)
This article was a philosophical review of Emmanuel Levinas thought which is synthesized with the idea of humanity. Levinas began the ethical thought by discussing the concept of face that has implications for ethical responsibility towards others. This concept gives an understanding to the critique of all forms of totalization to the other or egology in the entire tradition of Western philosophy. Totalization was rooted in egocentrism which ultimately harms humanity. Upholding humanity associated with Levinas’s view was not a problem creating live in order and harmony, but rather it has been an ethical consequence of encountering the others. Ethical responsibility contains sensibility which is root of all solidarity, an attitude of respect for dignity of the others. As an endeavour to understand current humanity situation with linking the context of the present situation with the post-truth climate in social and political space, ethical responsibility and sensibility are important concrete offers that become an awareness in building humanity. Ethical responsibility and sensibility in Levinas’s philosophical thought were concrete insight to become an awareness in building attitude and mentality of humanity. This article used a qualitative method of literature study which theoretically also used interpretation and phenomenology as its content. Artikel ini merupakan suatu tinjauan filosofis mengenai pemikiran etika Emmanuel Levinas yang disintesiskan dengan gagasan kemanusiaan. Levinas memulai pergumulan etis dengan membahas konsep wajah yang berimplikasi pada suatu tanggung jawab etis terhadap orang lain. Tanggung jawab etis menjadi kritik terhadap segala bentuk totalisasi dalam memandang ‘Yang Liyan’ ataupun egologi dalam seluruh tradisi filsafat Barat. Totalisasi yang berakar pada egosentrisme pada akhirnya menciderai kemanusiaan yang merupakan ruang bersama manusia. Menegakkan kemanusiaan dikaitkan dengan pemikiran Levinas bukanlah sebuah problem keinginan untuk hidup teratur dan harmoni, melainkan sudah menjadi konsekuensi etis pertemuan dan berhadapan langsung dengan orang lain. Tanggung jawab etis mengandung sensibilitas yang menjadi dasar dari seluruh solidaritas, sikap penghargaan atas harkat dan martabat orang lain serta sikap respek terhadap cara berada atau mengada dalam kehidupannya. Dengan menghubungkan konteks situasi zaman kini dengan iklim pascakebenaran dalam ruang sosial dan politik, tanggung jawab etis dan sensibilitas adalah tawaran konkrit dalam membangun kesadaran kemanusiaan. Artikel ini menggunakan metode kualitatif studi pustaka yang secara teoretis juga menggunakan interpretasi dan fenomenologi sebagai muatannya.